Clinical Evaluation of Phyto-formulation for Canine Distemper Virus by ELISA - V. Manikandan; G. Sathish; Kurunchi C Divya; D. Suresh; K. Murugan; A. Nizamuddin; Mohamed Arif (The Indian Veterinary Journal, 2025)
Canine Distemper virus (CDV) is a highly contagious and devastating infectious disease in canines, with higher incidence in young and unvaccinated puppies. Controlling CDV outbreaks is a challenge in developing countries especially for free-roaming dogs (FRDs) due to low CDV vaccinations. This study aimed to investigate the efficacy of a phyto-formulation consisting of Andrographis paniculata, Curcuma longa, and Tinospora cardifolia extracts against CDV in clinically infected dogs. Dogs presenting suggestive symptoms of CDV such as increased body temperature, ocular and nasal discharge, seizures, temporal twitching, and digestive disturbances were included in the study. A randomized controlled clinical trial was conducted, with dogs categorised into two groups: a control group received standard antibiotics therapy and supportive treatment, and treatment group received phytoformulation. Clinical signs were monitored throughout the study period. The phyto-formulation demonstrated potential action in reducing the severity of the clinical signs associated with CDV infection. Antigen ELISA tests revealed a decrease in the serum antigen levels in the treated groups compared to the control group on day 7 (0.45 ≤ 0.01 vs. 0.59 ≤ 0.01), day 14 (0.37 ≤ 0.001 vs. 0.67 ≤ 0.001), day 21 (0.28 ≤ 0.001 vs. 0.62 ≤ 0.001) respectively. The phyto-formulation comprising Andrographis paniculata, Curcuma longa, and Tinosporacardifolia extracts demonstrated ameliorative potential in mitigating the clinical signs and modulating the immune response against CDV in infected dogs.